TIMELESS DESIGN EMBRACING SUSTAINABILITY THROUGH BRAND COMMUNICATION STRATEGIES: A STUDY OF INDIAN APPAREL BRANDS - Ahiwale, Nachiket; Kaushik, Hemant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sustainability goes beyond the label. It’s not just a green logo stamped on a product, but a deep commitment woven into the fabric of a brand, reflected in the actions behind the scenes. However, it reflects how the brand communicates its identity in the domestic and international markets to sustain its identity in a longer race in response to other competitive brands. India currently houses more than 1400 large textile companies and around 1.5 million small and medium enterprises. Indian celebrity apparel brands such as Rheson by Sonam Kapoor and Indian apparel brands such as Patanjali Paridhan and Craftsvilla, are successful in terms of initial launch but later end up in terms of brand growth due to a lack of brand communication and brand strategy. Whereas other brand products, such as Jaypore, Raymond and Fabindia can create an impact in terms of brand growth by combining motion graphics, artificial intelligence, cinematography, powerful visual merchandising, 3D art installations, and the art and power of storytelling to promote the identity of different products through different visual elements that speak about the product’s functionality. The purpose of this research paper is to build the brand product category’s emotional relationship with the user, extend the product’s lifespan in the customers hearts, and promote brand identity.